IMPLEMENTASI MODEL PROBLEM BASED LEARNING DENGAN MEDIA POWER POINT PADA PEMBELAJARAN IPAS KELAS V SD - Irawan Kurnianto; Eka Zuliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of technology in the digital era demands fundamental changes in the education systemThe purpose of this study is to explore strategies for developing 21st-century skills through the use of Canva media in the Problem Based Learning (PBL) learning model on statistics material at the elementary school level. The subjects of this study were 25 5th grade students of SD 7 Bulungcangkring. This research is a case study research that uses various data collection techniques, including interviews, observations, and questionnaires The results of the study showed that there was significant development in 21st-century skills that occurred to students when implementing PBL learning models with power point media.